The Use of Modern Technology in Journalistic Production (NTU journal for Administrative and Human Sciences (JAHS), 2022)
Press release is a technical and journalistic process that has an aesthetic and functional character. It is an important step in publishing the newspaper, which is concerned with presenting the editorial material on the page in an attractive and eye-catching manner. The sharp competition between newspapers of different directions has led to the search for ways to confirm their survival and continuity and to highlight their personality. Printing and adapting it in line with the content and general policy of the newspaper.Among the most prominent developments that the press has witnessed in terms of digital computer technology and network communication technology (the Internet), is the emergence of electronic press websites, which prompted designers and directors to find new methods and techniques, to design and produce pages, taking advantage of what the Internet provides of patterns, journalistic technical templates and new technologies in the field of Press directing, as the Internet has contributed to the development of press production through the emergence of new directing methods, and a set of design programs and programming languages ??for websites.